2007
DOI: 10.1002/jhm.172
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of estimated glomerular filtration rate: Effect on physician recognition of chronic kidney disease and prescribing practices for elderly hospitalized patients

Abstract: BACKGROUNDPhysician recognition of chronic kidney disease (CKD) in elderly patients has been noted to be poor. These patients are at increased risk of medication dosing errors and acute renal failure.OBJECTIVETo investigate the effect of reporting estimated glomerular filtration rate (GFR) of elderly hospitalized patients on physician recognition of CKD and physician prescribing behaviors.DESIGNA retrospective combined with a prospective medical record review project.SETTINGA large academic medical center.PATI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…The authors concluded that although eGFR reporting improved recognition of CKD among physicians, it did not lead to a change in physician prescribing behavior. Based on our results and those of Quartarolo et al, 31 we believe that poor knowledge of renal dosing …”
Section: Discussionmentioning
confidence: 59%
“…The authors concluded that although eGFR reporting improved recognition of CKD among physicians, it did not lead to a change in physician prescribing behavior. Based on our results and those of Quartarolo et al, 31 we believe that poor knowledge of renal dosing …”
Section: Discussionmentioning
confidence: 59%
“…At least 3 studies have assessed the effects of eGFR reporting on clinician recognition and behavior. [17][18][19] Two of these, which included only reporting, found only modest increases in physician recognition. A third study, which included an educational intervention as well, noted a 4-fold increase in detection rates.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Whether such recognition leads to changes in physician practice which may slow the progression of chronic kidney disease is unclear. Specifically, if CKD is recognized, are physicians more likely to prescribe ACE inhibitors or ARBs, and are they less likely to prescribe drugs that are nephrotoxic or have increased side effects in CKD?…”
Section: Introductionmentioning
confidence: 99%
“…Although nephrology consultation may often be needed, we do not see it as mandatory or even desirable in every case. Publications reviewing experiences with eGFR suggest that reporting it increases awareness of CKD but emphasize the need for education as an adjunct (27)(28)(29)(30). The American Society of Nephrology in collaboration with the National Kidney Disease Education Program provides a free slide set at its web site.…”
mentioning
confidence: 99%